Development of Collaborative Digital Module on Zedemy Platform to Improve Student Engagement - Ririanti Rachmayanie Jamain; Hendro Yulius Suryo Putro; Muhammad Indra Sadewa (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2022)
During the Covid 19 pandemic, lecture activities in the Guidance and Counseling study program were transferred to online media through the e-learning platform of the Integrated Lambung Mangkurat University Information System (SIMARI). This study aims to produce collaborative digital modules through the zedemy platform used in lectures in the Guidance and Counseling study program, determine the feasibility of collaborative digital modules and determine the level of student engagement in using collaborative digital modules. ASSURE model development research (Analyze Learner, State Objective, Select Methods, Media and Materials) choosing to conducted on students of the Guidance and Counseling Study Program at Lambung Mangkurat University to determine student engagement with the use of modules. Module validation is carried out by material experts, media experts, and students. The feasibility of collaborative digital modules through the zedemy platform was assessed using a media expert eligibility sheet, material expert, and student involvement questionnaire in using the module. The results indicate the feasibility of the collaborative digital module shows a very feasible category in terms of media with a 103 of a maximum score of 116. Feasibility on the material aspect shows a very feasible category with a score of 97 out of a maximum score of 108 (89.81%). Student engagement showed a significant increase as indicated by the t-test results, obtained sig = 0.000. The mean of pretest = 55,35 and at posttest = 73.97. There is an increase in student engagement when using collaborative digital modules through the zedemy platform.